Serum Hemoglobin and Potassium Levels in Sudden Cardiac Death at Hemodialysis Center of Aziz Bhatti Hospital Gujrat - Rohail Razzaq, Javeria Sajjad, Ashfaq Ali, Hajra Sultan, Muhammad Tehseen Hussain, Samreen Tahir, Hasnat Shabbir (Pakistan Journal of Medical & Health Sciences, 2023)
Background: Sudden cardiac arrest has become a serious pandemic and a substantial public health burden. Significant morbidity and death are linked to it. Hemodialysis is considerably a heavy burden on cardiac patients. A sudden cardiac arrest is sometimes a disastrous event that happens without warning and is regrettably a significant cardiac disease manifestation in individuals surviving on kidney dialysis. Aim: To determine Serum Hemoglobin and potassium levels in sudden cardiac death patients admitted in hemodialysis center of Aziz Bhatti Shaheed Teaching Hospital Gujrat. Study Design: Cross-Sectional Study Methodology: This research study was conducted at the hemodialysis center of Aziz Bhatti Shaheed Teaching Hospital Gujrat. The Ethics Committee approved to conduct of this descriptive cross-sectional study on 40 (20 males and 20 females) sudden cardiac patients. All information and the goal of the research project were explained to patients or their relatives before the collection of blood serum. Prescription drug lists, smoking histories, and medication or dialysis report data were randomly evaluated. Laboratory results from recent month were collected, together with dialysis run sheets and cardiac arrest data forms. Results: Results of this result study showed that the mean value of age was 50 years with a mean standard deviation of 15.1 (p= <0.001). The mean BMI (kg/m2) was estimated as 26.8 with a mean standard deviation value of 2.6 (p= 0.01). Almost 21.6% of male patients were smokers and overall 36.1% were associated with cardiac arrest due to coronary artery disease. Systolic blood pressure (mmHg) was 165 (95% CI of 117-140) (p= <0.001), diastolic blood pressure (mm Hg) was 89 ( 95% CI of 64-72) (p= <0.001), hemoglobin level was 0.73 (95% CI of 0.70-0.76) (p= <0.001), Hemoglobin A1 c was 6.4% (95% CI of 5.8-7.6) (p= <0.001), Urea was 56 (95% CI of 41-79) (p= <0.001), and estimated glomerulus filtration rate (mL/min per 1.73mm2 ) was 1.16 (1.10-1.22) in sudden cardiac patients with low K (serum <4.0mmole/L). For the sudden cardiac patients with higher K level (serum >4.0mmole/L) showed that there was a significant change in the estimated values i.e. estimated glomerular filtration rate (mL/min per 1.73 mm2) was 0.67 (95% CI of 0.54-0.58) (p=<0.01). The practical implication of this research study suggests that the higher proportion of cardiac patients were reported higher concentration of K level serum. For diagnosis purposes K-level was directly associated with the cardiac disease progression. Conclusion: Hemodialysis patients with sudden cardiac arrest had reported very low concentrations of potassium levels. Dialysate prescriptions should be continuously reviewed and changed, especially after hospitalization in high-risk patients, to lower the risk of adverse cardiac events during hemodialysis. It was suggested that in the high-normal range of serum potassium seems to be safe and is linked to better outcomes. Keywords: Sudden cardiac arrest, Hemodialysis, serum potassium level, Hemoglobin